Ab initio study of the diffusion and decomposition pathways of SiHx species on Si(100) - Ceriotti, M; Cereda, S; Montalenti, F; Miglio, L; Bernasconi, M (2009)
Diffusion and decomposition of SiHx species adsorbed on the clean Si(100) surface are processes of relevance for the growth of crystalline silicon by plasma-enhanced chemical vapor deposition. In this work, we report an extensive search of diffusion and decomposition pathways for SiH3, SiH2, and SiH by means of combined ab initio metadynamics simulations and optimization of minimum-energy reactions paths. We find that on the clean surface SiH3 undergoes stepwise decompositions into Si and H adatoms according to SiH3 → SiH2 +H→SiH+2H→Si+3H with an overall reaction barrier of the order of 0.8 eV, consistent with the scenario inferred from secondary ion mass spectroscopy data. The lifetime of SiH3 at room temperature calculated within transition state theory in the harmonic approximation is in agreement with experiments. The lifetime of SiH2 turns out to be similar to that of SiH3. Possible trap states for SiH2 are proposed, based on energetics and by comparing calculated scanning tunneling microscope images with experimental data. © 2009 The American Physical Society.